Ubuntu, Umuntu and Ubuntu: A Response to Matolino and Kwindingwi - Motsamai MOLEFE; Elphus MUADE (Arụmarụka)
The paper proffers a response to Bernard Matolino’s and Wenceslaus Kwindingwi’s rejection of UBUNTU. To do so, the paper does three things. First, it clarifies important concepts of Ubuntu ethics. That is, it distinguishes among the concepts of Ubuntu (African philosophy), ubuntu (virtue or excellence) and umuntu (a human being and the value of human dignity associated with her/him). Second, it proffers a defense of Ubuntu ethics, which it [Ubuntu ethics] will construe as a perfectionist moral theory that requires the agent to perfect herself/himself by developing ubuntu (the final good). Finally, the paper provides reasons why we should not call for the end of Ubuntu ethics by suggesting how it (Ubuntu ethics) has conceptual, moral and political resources – such as human dignity and ubuntu – to construct a robust polity.